Morpho-syntactic errors of ESL learners' written essays : a Minimalist Approach / Mohammed Adam Mohammed Taha - Mohammed Adam, Mohammed Taha (2012)
This study aims to investigate and analyze morpho-syntactic errors on ESL learners’ essays; it attempts to identify these errors, justifies and provides evidences, and establishes how lexical information affects the sentential structure. The subject of this study comprises of 36 narrative essays written by Sudanese university students, Minimalist Program is used as analytical tool. The results revealed that, agreement features, inflectional morphology, categorical features, and lexical projections of TP to be errors found in the study. I addition the lexical item has an effect on both logical form (meaning) and sentential structure (syntax). Overall, it’s possible to encourage our teachers of ESL to do extensive practice and exposure instruction toward their students since all reviewed studies indicated the consistence of the similar errors in writing as the skill in second language acquisition.